President Bierut’s Pardons. The Treatment of petitions for Pardon of Persons Convicted by Courts Mortial in 1947-1952 (Archives of Criminology, 1995)
The study deals with the procedure and practice of granting pardons by the President of Republic of Poland Bolesław Bierut to persons convicted ty mortial courts. Analyzed have been the years 1947–1952, that is President Bierut’s term in office. Before, in the years 1944–1947, he was President of the National People’s Council, and afterwards, from 1952 till his death in 1956 – President of the Council of State. The 1947–1952 period has been selected for analysis not only for the above formal reason of President Bierut’s term in office. Bierut had the powers to grant pardons also as President of the National People’s Council (1944–1947) and, later on, as President of the Council of State (1952–1956). Thus the years 1947–1952 have been chosen for substantive reasons, too, as they were the period of particularly intense penal repression applied by courts mortial in Poland. It was directed chiefly against political opponents – real and alleged alike – of the new regime. Finally, the archival resources of the Civil Chancellery of President of Republic of Poland, kept in the Archives of New Files in Warsaw, make it possible in principle to fully reconstruct the procedure and practice of granting pardons.In the years 1947–1952, while holding the office of President of Republic of Poland, Bolesław Bierut was also leader (lst Secretary) of the ruling Colmmunist Party: first the Polish Workers’ Party and then, from December 1948 on, Polish United Workers’ Party.The author discusses the particularly repressive nature of law as applied by courts mortial to which also common courts reported. He also points out that the law was infringed quite freely by the investigating agencies, public prosecutors, and finally by courts mortial. Severe penalties were therefore imposed not only on the real but also on alleged opponents of the new regime.The investigating and prosecuting agencies concocted criminal cases of persons who were innocent under the law, and the courts sentenced those persons. This way, the Polish administration of justice was involved in political struggle. Its ideological justification was provided by Joseph Stalin’s theory of intensification of class struggle with progressing building of so-called “socialism” which found it legal expression in a theory, formulated by a Soviet politician and lawyer Andrei Vishinsky, on the defendant’s admission of guilt (forced by torture, of course) as the crown evidence in judicial proceedings.The author stresses that in his capacity as leader of the ruling Party and at the same time Head  of State, Bolesław Bierut actually initiated many political trials based on faked investigation and often leading to the defendant being sentenced to death by a court mortial. According to the statutory procedure, such defendants then petitioned President Bierut for pardon which means that the case actually made a full circle. The author states that the middle level agencies of administration of justice notified the leaders of the ruling Party of glaring breaches of the law but the information never met with any response.The author points to numerous formal defects in the application of the pardon procedure; for example, some decisions refusing pardon do not even bear the President’s signature. The petitions, filed by the convicted person or his family or examined ex officio were in most cases accompanied by a negative opinion of the Supreme Military Court and Chief Military Prosecutor’s Office. There were cases in which a person sentenced to death in summary proceedings was actually executed without the obligatory pardon procedure. In one case, pardon was probably refused after the actual execution. The opposite also happened: convicted persons were not executed despite the fact that pardon had been refused to them. The reason was that they were needed in other penal proceedings.The duration of pardon proceedings – of special importance in the case of death sentences – was not regulated by law and ranged from three days to three months.The author analyzes petitions for pardon filed by persons convicted by courts mortial. There were the total of 2,591 such petitions, including 1,813 (about 70%) filed by persons sentenced to capital punishment. The President of Republic of Poland pardoned 589 persons or 32% of all those sentenced to death. There were among them both common criminals and political offenders. It is most difficult to guess the motives of the President (or his closest associates) which guided his decisions on pardon. In some cases, he simply followed the opinion of persons with whom he reckoned. The President’s discretion – the essence of the right of pardon – can be supposed to have played the smallest part.The procedure and practice of the exercise by President of Republic of Poland of his right of pardon was among the elements of the practice of lawbreaking in Poland in the years 1947–1952.